Preliminary study on the effects of storage condition on the quality of commercially processed soy milk. - Palmares, Roy Samuel V.
The study aimed to determine the effects of storage conditions on the quality of commercially processed soy milk. Two brands were purchased a grocery store and both have similar packaging material. The samples were divided into two equal numbers and stored at chilled and room conditions for 26 days. The physiochemical properties like pH and TSS (°Brix) were monitored while the microbiological quality was expressed in terms of anaerobes and the aerobic plate counts. The results of T-test for all parameters did not show a significant difference except for pH value. The samples stored at room conditions showed a low pH value, which can be due to biochemical reactions such as the conversion of sugars. It is recommended that when conducting similar study, the actual temperature for storage should be closely monitored to stimulate conditions of warehouses or retail stores.